Clinical performance of metagenomic next-generation sequencing for diagnosis of pulmonary Aspergillus infection and colonization - Jiang, Ziwei; Gai, Wei; Zhang, Xiaojing; Zheng, Yafeng; Jin, Xuru; Han, Zhiqiang; Ao, Geriletu; He, Jiahuan; Shu, Danni; Liu, Xianbing; Zhou, Yingying; Hua, Zhidan (Frontiers in Cellular and Infection Microbiology, 2024)
Background: Investigations assessing the value of metagenomic next-generation sequencing (mNGS) for distinguish Aspergillus infection from colonization are currently insufficient.The performance of mNGS in distinguishing Aspergillus infection from colonization, along with the differences in patients' characteristics, antibiotic adjustment, and lung microbiota, were analyzed.The abundance of Aspergillus significantly differed between patients with Aspergillus infection (n=36) and colonization (n=32) (P < 0.0001). Receiver operating characteristic (ROC) curve result for bronchoalveolar lavage fluid (BALF) mNGS indicated an area under the curve of 0.894 (95%CI: 0.811-0.976), with an optimal threshold value of 23 for discriminating between Aspergillus infection and colonization. The infection group exhibited a higher proportion of antibiotic adjustments in comparison to the colonization group (50% vs. 12.5%, P = 0.001), with antibiotic escalation being more dominant. Age, length of hospital stay, hemoglobin, cough and chest distress were significantly positively correlated with Aspergillus infection. The abundance of A. fumigatus and Epstein-Barr virus (EBV) significantly increased in the infection group, whereas the colonization group exhibited higher abundance of A. niger.Conclusions: BALF mNGS is a valuable tool for differentiating between colonization and infection of Aspergillus. Variations in patients' age, length of hospital stay, hemoglobin, cough and chest distress are observable between patients with Aspergillus infection and colonization.